Alendronate release from calcium phosphate cement for bone regeneration in osteoporotic conditions. Issue 1 (December 2018) - van Houdt, Claire; Gabbai-Armelin, Paulo; Lopez-Perez, Paula; Ulrich, Dietmar; Jansen, John; Renno, Ana; van den Beucken, Jeroen
Abstract Osteoporosis represents a major health problem in terms of compromising bone strength and increasing the risk of bone fractures. It can be medically treated with bisphosphonates, which act systemically upon oral or venous administration. Further, bone regenerative treatments in osteoporotic conditions present a challenge. Here, we focused on the development of a synthetic bone substitute material with local diminishing effects on osteoporosis. Composites were created using calcium phosphate cement (CPC; 60 wt%) and polylactic-co-glycolic acid (PLGA; 40 wt%), which were loaded with alendronate (ALN).In vitro results showed that ALN-loaded CPC/PLGA composites presented clinically suitable properties, including setting times, appropriate compressive strength, and controlled release of ALN, the latter being dependent on composite degradation. Using a rat femoral condyle bone defect model in osteoporotic animals, ALN-loaded CPC/PLGA composites demonstrated stimulatory effects on bone formation both within and outside the defect region.